Marital Compatibility and its Relation to Occupational Stress among Working Women in Government Departments in Al Batinah South Governorate, Sultanate of Oman - Al Ghafry, Asya Saeed Salem; Al Khawaja, Abdul Fattah (Journal of Humanities & Social Sciences, 2018)
The study aimed to identify the relation between the marital compatibility and occupational stress among working women in Government Departments in Al Batinah South Governorate, Sultanate of Oman. This study was conducted on 150 working women (i.e. 4.1% of the original study population). The researcher used the Dyadic Adjustment Scale (DAS; Spanier, 1976) translated by (Frisa, 2013) and the Occupational Stress Scale (Al-Ghadaniyah, 2011), adopting the correlative descriptive approach throughout the study. The results showed a statistically significant reverse correlation at (α ≥ 0.01) between the marital compatibility and the occupational stress. Thus, the more the marital compatibility increases, the more the occupational stress decreases and vice versa among working women. In addition, the marital compatibility was predictor of the occupational stress level, since it explained about 13% of the variance in the occupational stress.